»Mit navn er Boye, jeg graver dysser og gamle høje« - Stensager, Anders Otte (Kuml, 2003)
»My name is Boye, I dig carins and old mounds« The archaeologist Vilhelm Christian Boye The story of Vilhelm Boye is the history of one man’s passionate and insightful involvement in archaeology, which from the first was directed solely towards the Bronze Age. His involvement led to an academic disaster in his youth, but left behind it a developed skill in field archaeology. Despite his problems he persisted with what most obsessed him, namely the preservation of Denmark’s oak coffin graves. His multi-facetted personality and his more popular approach to archaeology may have challenged his contemporaries, and certainly contributed to his more or less deliberate exclusion from a permanent appointment at the Museum of Northern Antiquities in Copenhagen. Even though he was opposed by powerful people within the Copenhagen museum establishment for nearly twenty years, he had the natural facility of easily winning the trust of others. This enabled him to cope with the situation and turn it to his advantage wherever he found himself. His marriage to Mimi Drachmann brought a welcome stability to his life, but his lack of professional recognition and his exclusion from a place at the top of archaeology continued. Time was running out for Boye, but he managed to leave an impressive body of published work behind him. Vilhelm Christian Boye was the son of the Norwegian-born priest and writer of hymns Caspar Johannes Boye. In 1848 his father was moved to the garrison church in Copenhagen, where the family lived at 29 Bredgade until his father’s death from cholera in 1853. This was a fashionable part of town, its residents including both the composer Niels W. Gade and Professor Adam Oehlenschläger, and even more notably J.J.A. Worsaae lived in the same property as the Boye family from 1850 to 1852. It was probably through his neighbour Worsaae that Boye later became a member of the circle around C.J. Thomsen. We may therefore assume that Boye visited and spent many after-school hours at the Museum of Northern Antiquities, and soon became an assistant during the public tours. Early in the 1840s tension arose between Worsaae and Thomsen, because Thomsen did not want to make Worsaae a junior museum inspector. Worsaae had not hitherto received any stipend or official position, and with some justice felt himself hard done by. Thomsen however did not respond to his request, so he left the Museum, later to be made Director for the Preservation of Ancient monuments. At the same time he taught at Copenhagen University, where Boye from time to time came to his lectures. There is no doubt that Boye wanted an academic career, and presumably hoped that his involvement with the Museum of Northern Antiquities would allow him to complete a study of Scandinavian archaeology. In the meantime Boye studied at the Museum under the direction of both Thomsen and Herbst. In early October 1857 Boye undertook one of his first excavations of a Bronze Age mound, the so-called Loholm barrow at Snørumnedre Mark (fig. 1). The dating of the grave however caused problems for him, but through a comparative study of Bronze Age burial rituals he concluded that the grave had close parallels within this period. The following year three funerary urns and some bronze objects were found in Hullehøj barrow, near Kjeldbymagle on the island of Møn. The barrow was going to be blown up, but the local judge had the work stopped and sent Boye to lead the excavation in May 1859. As the excavation progressed, Boye was able to ascertain that there were both cremations and inhumations in one and the same barrow. The inhumations were surrounded by fist-sized stones and placed at the bottom of the barrow, the cremations higher up within the mound. In comparison with his earlier barrow excavations it is worth noting Boye’s stratigraphic observations, which for the first time supported the division of the Bronze Age into an earlier and a later section. This hypothesis had been suggested earlier, but not hitherto adequately demonstrated. In 1859 Boye published the results of his excavations of 1857-8, as well as those of his recently completed excavation of Aasehøj barrow at Raklev, in the periodical Annaler for Nordisk Oldkyndighed og Historie for 1858. This article is his first independent scientific publication, and should have attracted greater attention than it in fact did. In modern perspective the article is a perfectly competent archaeological publication, in which Boye solely through field observations reaches the conclusion that the Bronze Age could be divided into two periods, each with its own burial ritual. Even though Boye had been close to understanding why both cremations and inhumations occurred in the same barrow as early as 1857, he did not reach his final understanding this early. In November 1857 Worsaae had in fact given lectures at the university in which he suggested a division of the Bronze Age, but it is noteworthy that he had not earlier published any or all of his conclusions. His work on the subdivision of the Stone Age was probably more important to Worsaae, while the subdivision of the Bronze Age was more of a footnote, a natural outgrowth of the idea that there was continuous development from one stage to the next. Boye’s article in Annaler thus inevitably supported Worsaae’s hypothesis, although this was presumably not the intention. On the contrary, Boye merely intended to publish his own conclusions. Boye cannot therefore be said to be the sole originator of the subdivision of the Bronze Age, but apart his barrow investigations there was nobody else who reached the same conclusion at the time independently of Worsaae. In 1860 Boye took part in the first major bog excavations, at Vimose and then at Thorsbjerg with Engelhardt. Despite adverse circumstances and appalling weather, the Thorsbjerg excavations produced several important finds including Roman coins, a gilt breastplate, and also a very unusual face mask of silver with gilt (fig. 2). Although Engelhardt did not publish the full excavation report until 1863-69, Boye presented his observations in Annaler as early as 1860, where he discussed earlier interpretations of the many weapons found in bogs. Boye observed that the universal destruction of these weapons did not happen by chance, but was deliberate. Furthermore, the weapons lay in groups of one type, and the shields were pierced by spear points to pin them to the bottom of the bog. Boye’s interpretation of the finds was thus remarkably accurate, because he regarded them as votive offerings of the spoils of war. When Prussian and Austrian troops crossed the Ejder River on 1st February 1864, Boye volunteered within the month and was promoted to lance corporal (fig. 3). In May he was landed to take part in the defence of the island of Als along with the other Danish forces. On his return home in August Boye continued his work at the Museum of Northern Antiquities, but Thomsen’s health was failing, and after a long illness he died on 21st May 1865. The question of who was to succeed Thomsen had long been discussed, and it was indeed Worsaae who was appointed. Although Herbst had been groomed for the job by Thomsen, he found himself outmanouevred. Boye probably already knew by then that he would not be given a position at the Museum. Herbst, his confidant, could no longer help him, and Thomsen’s awareness of his archaeological skills was of no use either. Circumstances thus forced Boye to leave the Museum. Boye’s relationship with the family friend and poet H.C. Andersen resulted in the latter recommending Boye in December 1867 as a Danish tutor to the Brandt family in Amsterdam (fig. 4). On Wednesday 22nd January 1868 Boye departed for Amsterdam via Kiel. During his stay Boye wrote regularly to Andersen, who also travelled to Amsterdam to visit him. His stay in Amsterdam was evidently good for Boye, and contributed to the fact that he never lost his love for archaeology. As early as late August of the same year, Boye travelled to southern Halland in Sweden at the request of Ritmester Peter von Möller, to examine and excavate a large group of barrows known as the Ätterhögar on the Drömmestrup estate, the excavation of which was concluded in early July 1869. Boye thus returned home just in time to take part as a member of the Danish Committee in the International Congress of Archaeology and Anthropology that was held in Copenhagen from 25th August to 5th September. But his love of Schleswig and the old borderland called him, and soon Boye moved permanently to Haderslev to work as a freelance writer on the daily paper Dannevirke under the editorship of H.R. Hiort-Lorenzen. His coverage of the International Congress of Archaeology and Anthropology meeting in Copenhagen is the most extensive of Boye’s writings in Dannevirke. He also wrote a series of articles with a marked archaeological-ethnographic content, for example on the antiquities of Brazil, and the discovery of Australia. Although Boye supported himself as a writer for Dannevirke, his main occupation seems rather to have been the investigation of the burial mounds of Schleswig, which before 1864 had only been intermittently examined by amateurs. Boye began an extensive programme, and without his efforts and initiative, knowledge of many Schleswig barrows would have been lost. Although the information he recorded was not particularly satisfactory, in that it was mostly based on the memory of local people, his efforts should be seen as a precursor, because the work of protection went slowly at the time. In his search for lost information, in 1875 Boye considered the barrow at Dybvadgård north of Åbenrå, which had been partially excavated by Prince Carl of Prussia in 1864. During the excavations the Prince’s soldiers found an oak coffin, which was despatched to the Museum für Völkerkunde in Berlin. Boye therefore wrote direct to the Prince, who in reply sent a photograph and description of the coffin. During the next eight years Boye managed to accumulate a great deal of information about the barrows of Schleswig, but his work was not without risk, because several of his “missions” involved evading the Prussian authorities and their power to confiscate the antiquities which Boye from time to time illegally sent to the Museum in Copenhagen. In 1874 the Principal of Herlufsholm School, C. Hall, engaged Vilhelm Boye to organise the school’s collection of antiquities, which had been in store for nearly twenty years. In addition to this reorganisation, funds were also made available for the systematic excavation of a nearby barrow at Grimstrup (fig. 5). The barrow however contained very little, mainly urns full of cremated bone, but the excavation was thoroughly recorded and a series of drawings was produced by R. Bertelsen, the school’s teacher of drawing. After this Boye set to work to display the collection in the six cases that were made available. The greater part of the collection came from the Stone Age, filling no fewer than five cases, giving an impression both of coastal finds from shell middens, and grave finds. The Bronze Age display contained only a few bronzes, but rather more pots. Iron Age artifacts were hardly represented at all, and consisted mostly of whetstones, a bowl-shaped buckle, and a pot burnt black. In November of the same year Boye was working at Herlufsholm, he produced his remarkable work Vejledning til Udgravning af Oldsager og deres foreløbige Behandling [Guide to the Excavation of Antiquities and their Initial Study], published under the auspices of the Society for the Historical-Antiquarian Collection in Århus. Boye’s Guide is the first of its type, and one can clearly detect his close association with Herbst, who had contributed to the scientific content of the work. Boye’s link with the antiquarian collection in Århus had not come about by chance. During his time at the Museum of Northern Antiquities he had early on made contact with the person mainly responsible for the establishment of the Århus collection, Edvard Erslev. Boye joined the museum in 1871, re-arranged the collection, and produced a guide for visitors. For the first time the museum acquired a new and professional look. Boye thus functioned as part of the leadership until 1876, when he gave up his museum post in favour of the schoolteacher Emmerik Høegh-Guldberg. The continued problems facing Dannevirke and Hiort-Lorenzen’s mounting confrontation with the judicial authorities in Flensborg probably caused Boye to consider his position with the newspaper. This culminated with the expulsion of Hiort-Lorenzen, who then took up the post of chief editor of Nationaltidende in Copenhagen. Boye also travelled to Copenhagen in early 1878, and on 15th November the year after he married Mimi Drachmann, sister of the poet Holger Drachmann (fig. 6 ). Not suprisingly, Boye got a job at the Nationaltidende, where he edited the newspaper’s Archaeological and Ethnographic Communications until 1885. In the seven years Boye worked at the paper, no fewer than 150 numbers of the Communications appeared, Boye writing more than 400 pages of them himself. The articles include a multiplicity of archaeological and ethnographic topics such as “Egypt’s Ancient Cultures” and “A Copper Age in Scandinavia”. In 1882 Count Emil Frijs of Frijsenborg commissioned Boye to catalogue and organise his estate’s collection of prehistoric and medieval objects, which came from the area round the lake and castle ruin at Søborg in northern Zealand. Attempts had been made to drain the lake since 1793, and several antiquities had been found at various times during the work. The recording project culminated in the publication of a small book, Fund af Gjenstande fra Oldtiden og Middelalderen i og ved Søborg Sø [Finds of Objects from the Prehistoric and Medieval Periods in and around Søborg Lake], which among other things contains some of the first photographic illustrations of Danish antiquities (fig. 7). Worsaae’s death in 1885 inaugurated a new era, and Herbst was finally able to take over the post of head of the Museum (fig. 8). Boye’s long friendship with Herbst had in the previous years resulted in him becoming a regional inspector for the Museum. Herbst was probably even then considering Boye for a future post in the Museum, and was indicating that he himself could not be overlooked when it became time to nominate a successor to Worsaae. After his appointment to the Museum of Northern Antiquities in 1885, Boye continued his activities as inspector in northern Zealand, and was frequently called when new finds were recovered from Bronze Age barrows. In contrast to Herbst, Boye rapidly fell in with the group of younger workers, particularly Henry Petersen (fig. 9). Over the years they became close friends with a common interest in new finds, as during the excavation of Guldhøj in 1891. Boye had no draftsman at the excavation, but he did have a local photographer who recorded some aspects of the opening of the first oak coffin. These are the first photographs ever to be taken during an excavation, even though photography by then was nothing new (fig. 10). With the reorganising of the National Museum, Boye was made senior assistant of the historical section on 1st April 1892, under Henry Petersen. He was responsible for the Museum’s archive and library, but fieldwork and travels are what particularly characterise his work in these years. When the small Bronze Age barrow on which the Glavendrup rune stone had been erected in 1864 was nearly completely destroyed by ploughing, Boye undertook a restoration of the barrow itself and the associated ship-shaped arrangement of stones in 1892 (fig. 11). The restoration’s outcome was the construction of a new barrow on which was placed the rune stone, and the re-erection of the stones in the ship arrangement. At the same time, chamberlain A. Oxholm undertook a small excavation of the Bronze Age barrow at Tårnholm, and recovered an oak coffin containing the remains of a woman, a fine necklace, a belt plate, and a small bronze dagger. Boye was immediately informed, and in connection with his investigations at Tårnborg was able to go to Tårnholm and lead a new excavation of the barrow, in which A.P. Madsen was also involved, and recover two more oak coffins (fig. 12). If we now consider Boye’s last major work, the publication of the major volume Fund af Egekister fra Bronzealderen i Danmark [Finds of Oak Coffins from the Danish Bronze Age], there are several indications that suggest that Boye began the work with the early intention that its coverage should be wide, and contain his long-term investigations into and knowledge of the country’s oak coffin graves. It is particularly noteworthy that his work as an archaeological journalist and with the Archaeological and Ethnographic Communications seems to have been a kind of precursor to this, as the last chapters contain sections that are clearly derived from his contributions to the Communications. The manuscript was completed in April 1896, and A.P. Madsen prepared for it no fewer than 27 full-page folio sized copperplates. The work was dedicated to “the veterans of Danish archaeology”, C.F. Herbst the museum director, and Japetus Steenstrup, with whom Boye had first collaborated more recently. His many years of a wandering existence and work-related disruptions had however told on him, and soon after the book was published Boye became ill. From his private correspondence from 1896 it emerges that Boye often had insufficient time to be with his nearest and dearest. Despite his illness he travelled one last time to visit relatives at Viken, but his illness worsened and he had to travel rapidly to Lund and on to Copenhagen. Boye died on 22nd September apparently as the result of a stroke, and was buried in Søllerød churchyard north of Copenhagen. Boye’s potential as a researcher was noticed early on by Thomsen, but just as quickly suppressed by Worsaae, who may more or less deliberately have sought to out-manoeuvre his colleague. Boye’s character and energy may have seemed a threat, and although he never finished an academic education he nevertheless displayed a remarkable archaeological acuity, but was unable to bolster his own reputation. Some of the blame for this must rest with the Museum’s aged leaders, who never supported or developed Boye’s evident skills to any great extent. It must also be stressed that some of Boye’s earlier career problems are closely connected to the lack of vision and jealousy of these same leaders. When he departed for Amsterdam Boye had no expectation of a Museum post, but despite this he intelligently kept up his contacts with Copenhagen, particularly with Herbst, knowing full well that Worsaae’s leadership would one day end. This somewhat bold presumption turned out to be correct, and helped his archaeological career. There is no doubt that Boye in his later years tried hard to recover his lost reputation and save his career from the disaster it suffered when he was younger, but the price was high and it also affected his health. We must today recognise that his reputation was restored to the highest level, and we must thank him for the fact that, through him, a uniquely detailed knowledge of the Bronze Age people themselves was preserved for Danish archaeology, as well as of their most prominent contribution to the Danish landscape: the barrows. Anders Otte Stensager Institut for forhistorisk arkæologi Københavns Universitet Translated by Peter Rowley-Conwy